2019
DOI: 10.1080/21664250.2019.1609712
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of wave propagation and transformation over a submerged reef

Abstract: In this paper, wave transformation over a submerged reef has been numerically studied based on the OpenFOAM model. This numerical model solves the Reynolds-Averaged Navier-Stokes equations for two-phase flow, and employs the volume of fluids (VOF) method for the free surface. The k-ω SST turbulence model is used to simulate wave breaking and the wave generation library waves2Foam is adopted to generate waves in the model. The numerical model is first validated against the physical experimental data, and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For these reasons, it has become increasingly important to develop methodologies and tools capable of forecasting and monitoring wind waves in reservoirs and stretches of waterway. In this sense, controlling the level of agitation of the reservoir's free surface and its effects on fixed or mobile structures and banks is, in fact, an essential element in building a basis for a future warning system [8,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it has become increasingly important to develop methodologies and tools capable of forecasting and monitoring wind waves in reservoirs and stretches of waterway. In this sense, controlling the level of agitation of the reservoir's free surface and its effects on fixed or mobile structures and banks is, in fact, an essential element in building a basis for a future warning system [8,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study was reported by Franklin et al [21], who analyzed the impact of reef roughness on the hydrodynamic characteristics across a reef at the laboratory scale using the RANS model. Li et al [22] evaluated the effects of varying fore-reef slopes and reef flat water levels on the regular wave interaction with an experimental reef via the RANS model together with a standard k-ω SST turbulence closure. Osorio-Cano et al [23] adopted a Large Eddy Simulation (LES) model to investigate cross-reef wave damping due to wave breaking and seabed friction based on a field reef profile.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it has become increasingly important to develop methodologies and tools capable of promoting the forecasting and monitoring of wind waves in reservoirs and stretches of waterways. In this sense, the control over the reservoir's free surface agitation level and its effects on fixed or mobile structures and on the margins is indeed an essential element in the construction of a basis for a future alert system (Diebold & Heller, 2017;Marques & Andrade, 2017;Mattosinho et al, 2018;Różyński, 2018;Jalil et al, 2019;Li et al, 2019;Mattosinho et al, 2019;Holanda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%